OPTIMALISASI MEDIA DAN TEKNOLOGI ASISTIF DALAM KURIKULUM MERDEKA BELAJAR DI SEKOLAH INKLUSI - Muhammad Nurrohman Jauhari; Sambira Mambela; Aulia Dwi Shanty; Dewi Nurmasari; Adela Hoar Usfinit; Agustina Batlyol (Kanigara, 2022)
The implementation of community service to provide knowledge and implementation of media and assistive technology in the Merdeka Belajar curriculum in inclusive schools. The implementation method is a). planning, b). implementation and c). evaluation. The results obtained based on the results of the training implementation can be concluded that the training carried out can provide knowledge and reinforcement for teachers in using learning media and assistive technology in the independent learning curriculum. The success of increasing participants' knowledge is shown by the average value of the pre-test results from 63.41 increasing to 82.25 in the post-test average value.